解方程log2(2x^2-x)=log2(x+1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:42:37
解方程log2(2x^2-x)=log2(x+1)解方程log2(2x^2-x)=log2(x+1)解方程log2(2x^2-x)=log2(x+1)log2(2x^2-x)=log2(x+1)2x^
解方程log2(2x^2-x)=log2(x+1)
解方程log2(2x^2-x)=log2(x+1)
解方程log2(2x^2-x)=log2(x+1)
log2(2x^2-x)=log2(x+1)
2x^2-x=x+1
2x^2-2x-1=0
x1=(1+根号3)/2
X2=(1-根号3)/2
又定义域是2x^2-x>0,x+1>0
x(2x-1)>0,x>-1
x<0,或x>1/2,且x>-1
即有-1
经检验,X1,X2都是方程的解.
2x^2-x=x+1
且x》0
2x^2-2x-1=0
解方程即可
解方程log2(2-x)=log2(x-1)+1
解方程log2(x+14)-log2(x+6)=3-log2(x+2)
解方程log2(2x^2-x)=log2(x+1)
解方程log2(2x+1)=log2(x^-2)
log2(x+1)+log2x=log2(6)解方程
解方程 log2(2^(x+1)+2)=2/log2((2^x)+1)log2(2^(x+1)+2)=2/log2((2^x)+1).thx.
解方程log2(4^x+1)=x+log2(2^(x+3)-6)
解方程log2^(4^x+4)=x+log2^[2^(x+1)-3]
解方程:log2(4^x+4)=x+log2(2^(x+1)-3)
解关于x的方程:log2(x+14)-log0.5(x+2)=3+log2(x+6)
log2(x²-2)=0解方程
解2log2^(x-5)=log2^(x-1)+1
方程log2(2^x+1)log2(2^(x+1)+2)=2的解
方程log2(2^x+1)log2(2^x+1)=2的解为
解方程log2(2x+1)=log2(x^2-2)
方程log2[9^(x-2) +7]=2+log2[3^(x-1) +1]的解为
方程log2(x-1)=2-log2(x+1)的解为
方程log2(9^(x-1)+7)=2+log2(3^(x-1)+1)的解?